1995
DOI: 10.1128/jcm.33.6.1496-1500.1995
|View full text |Cite
|
Sign up to set email alerts
|

Serologic detection of infection with cagA+ Helicobacter pylori strains

Abstract: Approximately 60% of Helicobacter pylori isolates possess the cagA gene and express its 120-to 140-kDa product (CagA). In this study, the cagA gene was detected in H. pylori isolates from 26 (81.3%) of 32 patients with duodenal ulcers (DU), 17 (68.0%) of 25 patients with gastric ulcers, and 23 (59.0%) of 39 patients with nonulcer dyspepsia (NUD). By Western blotting (immunoblotting) with antiserum to CagA, in vitro CagA expression was demonstrated for 95.5% of cagA ؉ strains compared with 0% of strains lacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
100
2
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(115 citation statements)
references
References 37 publications
12
100
2
1
Order By: Relevance
“…In this study, unlike the data previously reported [25,27], the magnitude of the anti-CagA titer (calculated by omitting subjects who were CagA negative but H. pylori positive) in DU patients was significantly higher than that of NUD patients. In contrast, no significant difference was observed between GU and NUD, even if GU patients showed anti-CagA titer higher than in NUD patients.…”
Section: Discussioncontrasting
confidence: 80%
“…In this study, unlike the data previously reported [25,27], the magnitude of the anti-CagA titer (calculated by omitting subjects who were CagA negative but H. pylori positive) in DU patients was significantly higher than that of NUD patients. In contrast, no significant difference was observed between GU and NUD, even if GU patients showed anti-CagA titer higher than in NUD patients.…”
Section: Discussioncontrasting
confidence: 80%
“…22,23 Anti-CagA antibodies in the serum and in the supernatants from gastric bioptic cultures have shown that CagA is produced in vivo 22,24,25 and that this protein is also detected more frequently in peptic ulcer patients than in patients with gastritis only. 22,24,26 There is also a high percentage of detection of anti-CagA antibodies in gastric cancer patients. 25 There is a growing body of evidence that the mucosal damage is partly caused by activation of leucocytes, with production of excessive amounts of ROM.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the cagA gene (or the CagA protein) has been associated with both duodenal ulcer and gastric cancer [29][30][31][32]. Although the function of CagA is unknown, it is generally accepted that the presence of CagA identifies infection with organisms containing the cag pathogenicity island (CPI) [33] and is a marker for infection associated with a higher level of inflammation than caused by H. pylori without the pathogenicity island [34,35].…”
Section: Caga Is a Marker For Enhanced Inflammationmentioning
confidence: 99%